Analisis Penetapan Harga Jasa Make Up Artist (MUA) Menggunakan Metode Cost Plus Pricing dan Metode Going Rate Pricing - Anggraeni, Rina; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to analyze the pricing of Make UpArtist (MUA) service at Erika Wedding Gallery Metro using two pricing methods, namely Cost plus pricing and Going Rate Pricing. the Cost Plus Priicng method involves adding a markup to the total production costs to determine the selling price, while the Going Rate Pricing method sets prices based on the rates prevailing in the market. The research uses a case study approach to understand how each method can be applied and its impact on pricing. Data was collected through in-depth interviews as well as analysis of operational cost. The research results show that the Cost plus pricing method provides a more stable and predictable price structure, while the Going Rate Pricing method is more responsive to market dynamics and competition, that optimizing strategy competitive and sustainable service prices